Assessment of OLCI absorption coefficients for non-water components across all optical water classes - Bracher, Astrid; Banks, Andrew Clive; Xi, Hongyan; Dessailly, David; Gossn, Juan; Lebreton, Carole; Röttgers, Rüdiger; Kwiatkowska, Ewa; Chaikalis, Spyros; Mehdipour, Ehsan; Pitta, Elli; Soppa, Mariana Altenburg; et al. (Frontiers in Remote Sensing, 2025)
New products of water-inherent optical properties have been made operational by European Organisation for the Exploitation of Meteorological Satellites (EUMETSAT), on behalf of the EC Copernicus Programme, based on a three-step semi-analytical algorithm to derive absorption coefficient products for all non-water components (anw), for phytoplankton (aphy), and for coloured detrital and dissolved matter (acdm), from the first eight bands of the Sentinel-3 (S3) Ocean and Land Colour Imager (OLCI). Additionally, based on a different type of retrieval, the absorption of coloured dissolved organic matter (CDOM) from the OLCI 443 nm band, acdom(443), has been introduced as a new product. In this study, we evaluate for the first time these new absorption coefficient products for OLCI, based on validation with a large (up to 1,000), global, and comprehensive in situ matchup dataset covering all optical water classes, considering the first 7 years of the S3 mission. Results show robust retrievals for all four OLCI absorption products (Rlog of 0.68–0.86), with a median absolute percent deviation of 30%–51% across all water types for the 443 nm band and similarly for the 400, 412, 490, and 510 nm bands. Performance was strongest for anw(λ) and weakest for acdm(λ). Results for these products for bands 560, 620, and 665 nm are much poorer. The results for OLCI anw(λ), aphy(λ), and acdm(λ) are consistent with previous in situ validation results presented for the European Seas. To obtain a good assessment on the temporal and spatial consistency, the monthly aphy(443) and acdm(443) data from 2019 have been intercompared with other operationally available products. The intercomparisons show that all products agree well for their 2019 average median value and in their overall regional distribution and seasonal variation. EUMETSAT operational processing now delivers the absorption products for the 443 nm band [aphy(443), anw(443), acdm(443), and acdom(443)] for S3 OLCI, and our study confirms the validity of these products. Furthermore, our study corroborates the skill of the EUMETSAT algorithm to obtain valid information in most of the blue and green spectra, making it of high potential for introduction into the processing of ocean-colour radiometry data from new hyperspectral satellite missions.